Cytotoxic Effect of Ink Extracted from Cephalopoda on Cancer Cell Line - Khudhair, Israa H.; Suker, Dhamia K.; Hanna, Balsam A. (Scientific Journal of Medical Research, 2019)
Objectives: The present study describes the biochemical, antioxidant and anticancer properties of the crude and melanin free ink of Sepia which is rich in both organic and inorganic components. Methods: The specimens of Sepia sp. were collected from Fao, South of Basrah /Iraq during November and December of 2018. They held the collected animals ventrally and squeezed the animal's posterior end to eject ink. The extracted ink samples both crude and melanin free ink were lyophilized, weighed and stored at 4°C until use .Then determination of the moisture, ash, total protein, lipid and carbohydrate in samples. The activity of ink as antioxidant was determination by the DPPH method. Finally, evaluation of anticancer activity by the MTT assay. Results: The quantitative analysis define the presence of protein (1.1 – 1.3 mg/ml), lipid (1.38 – 1.48 mg/ml), carbohydrates (0.01 –0.9mg/ml), ash (14and5%) and moisture (91.7-83.75 %) content.. The ink revealed good antioxidant activity, thereby lowering or retarding the initiation of lipid oxidation process. The ink was screened for its anticancer activity against human breast adenocarcinoma cell line (MCF 7) and it exhibited a strong cytotoxicity by inhibiting the cell growth. Conclusion: Thus the ink, especially the melanin free ink is known to possess significant potent antioxidant activity and anti-proliferative effect. The present study showed that the melanin free ink was richer in biochemical properties than the crude ink.